Age at menarche in Canada: results from the National Longitudinal Survey of Children & Youth - Hamadeh Mazen J; Ardern Chris I; Al-Sahab Ban; Tamim Hala (BMC, 2010)
Abstract Background Given the downward trend in age at menarche and its implications for the reproductive health and wellbeing of women, little is known about menarcheal age in Canada. Most Canadian studies are only representative of specific populations. The present study, therefore, aims to assess the distribution of age at menarche for Canadian girls and explore its variation across socio-economic and demographic factors. Methods The analysis of the study was based on all female respondents aged 14 to 17 years during Cycle 4 (2000/2001) of the National Longitudinal Survey of Children & Youth (NLSCY). The main outcome was age at menarche assessed as the month and year of the occurrence of the first menstrual cycle. Kaplan Meier was used to estimate the mean and median of age at menarche. Chi-square test was used to assess the differences in early, average and later maturers across the different levels of socio-economic and demographic variables. Bootstrapping was performed to account for the complex sampling design. Results The total number of girls analyzed in this study was 1,403 weighted to represent 601,911 Canadian girls. The estimated mean and median of age at menarche was 12.72 years (standard deviation = 1.05) and 12.67 years, respectively. The proportions of early (< 11.53 years), average (≥11.53 years and ≤13.91 years) and late maturers (> 13.91 years) were 14.6% (95% confidence interval (CI): 11.92-17.35), 68.0% (95% CI: 63.82-72.17) and 17.4% (95% CI: 14.10-20.63), respectively. Variations across the menarcheal groups were statistically significant for the province of residence, household income and family type. Conclusion The findings of the study pave the way for future Canadian research. More studies are warranted to understand menarcheal age in terms of its variation across the provinces, the secular trend over time and its potential predictors.